DYNAMIC SIMULATION AND EXPERIMENTAL STUDY ON RIGID-FLEXIBLE COUPLING OF SHEARER - ZHANG DongSheng; LI Yan; SONG QiuShuang (Jixie qiangdu)
In order to solve the problem of large deformation of the rocker arm, the virtual prototyping technology is used to soften the front and rear rocker arm, and the dynamic and mechanical model of the shearer is established. The strain gauge data of the picking sensor are obtained, and the load data is obtained by quadratic fitting the actual calibration of the sensor and the data, and the life prediction of the key components is carried out. The results show that the stress value and the load fluctuation value of the rocker joint pin are larger when the flexible deformation of the rocker arm is considered, which indicates that the flexible deformation of the rocker arm increases the vibration impact of the whole machine and reduces the strength of the shearer And the life expectancy of the shearer’s rocker pin, the fatigue life is 1.738×10~6 times, which proves the feasibility of the experimental method and provides the theory for the selection of the rocker pin in the actual working condition.